Emergence and clinical challenges of ST11-K64 carbapenem-resistant Klebsiella pneumoniae: molecular insights and implications for antimicrobial resistance and virulence in Southwest China - Linlin LI; Jiahui Liang; Huan Zhang; Jing Guo; Shan LI; Meng Li (BMC Infectious Diseases)
Abstract Background In clinical practice, the emergence of ST11-K64 carbapenem-resistant Klebsiella pneumoniae (ST11-K64 CRKP) has become increasingly alarming. Despite this trend, limited research has been conducted to elucidate the clinical and molecular characteristics of these strains. Objectives This study aimed to comprehensively investigate the clinical characteristics, antimicrobial resistance patterns, resistance and virulence-associated genes, and molecular epidemiology of ST11-K64 CRKP in Southwest China. Methods A retrospective analysis was performed on patients infected with carbapenem-resistant Klebsiella pneumoniae (CRKP) in a tertiary care hospital between July 2021 and May 2022. A total of 69 CRKP strains were isolated, with clinical data collected for detailed analysis. Laboratory assessments included antimicrobial susceptibility testing, hypermucoviscosity string testing, genotypic characterization of antimicrobial resistance and virulence genes, and multi-locus sequence typing. Statistical analyses were conducted using SPSS, with significance set at P < 0.05. Results Among the 69 CRKP isolates, 36 strains (52.2%) were identified as ST11-K64 CRKP. Hematological diseases were less associated with ST11-K64 CRKP infection compared to non-ST11-K64 strains (P = 0.012). However, central intravenous catheter use (P = 0.001), mechanical ventilation (P = 0.002), tracheal intubation (P = 0.006), and tracheotomy (P = 0.041) were significantly more common in ST11-K64 CRKP cases. Resistance rates to amikacin (P < 0.001), gentamicin (P = 0.004), tobramycin (P = 0.034), and sulfamethoxazole (P < 0.001) were significantly higher in ST11-K64 CRKP. Additionally, resistance-associated genes such as bla KPC−2 (P < 0.001) and virulence-associated genes including rmpA (P < 0.001), iucA (P < 0.001), rmpA2 (P < 0.001), and iutA (P = 0.001) were detected at significantly higher rates in ST11-K64 strains compared to non-ST11-K64 strains. Furthermore, compared to ST11-K47 CRKP, ST11-K64 CRKP harbored more virulence genes, such as rmpA (P = 0.007), iucA (P = 0.001), and iutA (P = 0.003). Conclusion Our findings underscore the rising prevalence of ST11-K64 CRKP, characterized by high levels of antimicrobial resistance and the presence of potent resistance and virulence genes. This strain poses a significant clinical and therapeutic challenge, necessitating heightened vigilance, stringent infection control measures, and robust clinical management strategies.